2018
DOI: 10.1038/s41563-018-0028-2
|View full text |Cite
|
Sign up to set email alerts
|

A facile approach to enhance antigen response for personalized cancer vaccination

Abstract: Existing strategies to enhance peptide immunogenicity for cancer vaccination generally require direct peptide alteration, which beyond practical issues may impact peptide presentation and result in vaccine variability. Here, we report a simple adsorption approach using polyethyleneimine (PEI) in a mesoporous silica micro-rod (MSR) vaccine to enhance antigen immunogenicity. The MSR-PEI vaccine significantly enhanced host dendritic cell activation and T cell response over the existing MSR vaccine and bolus vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
303
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 349 publications
(309 citation statements)
references
References 35 publications
6
303
0
Order By: Relevance
“…Both groups discovered that surface modification plays a major role in altering the inherent inflammatory response, leukocyte infiltration profile, and ultimately vaccine potency. In one study in 2018, the Mooney group adsorbed PEI to the surfaces of mesoporous silica microrods to enhance antigen immunogenicity via increased dendritic cell activation and CTL responses . In a second study in 2018, Mooney and co‐workers coated mesoporous silica rod scaffolds with lipid bilayers to mimic the endogenous ability of APCs to permit the fluid movement of antigens and costimulatory molecules within the membrane surface .…”
Section: Macroscale Materials For Immunotherapymentioning
confidence: 99%
“…Both groups discovered that surface modification plays a major role in altering the inherent inflammatory response, leukocyte infiltration profile, and ultimately vaccine potency. In one study in 2018, the Mooney group adsorbed PEI to the surfaces of mesoporous silica microrods to enhance antigen immunogenicity via increased dendritic cell activation and CTL responses . In a second study in 2018, Mooney and co‐workers coated mesoporous silica rod scaffolds with lipid bilayers to mimic the endogenous ability of APCs to permit the fluid movement of antigens and costimulatory molecules within the membrane surface .…”
Section: Macroscale Materials For Immunotherapymentioning
confidence: 99%
“…CD86 is a protein expressed on DCs that provides costimulatory signal necessary for T cell activation and survival, and the expression level of CD86 increases in the meantime when DCs are mature . TNF‐α, an important marker in the activation of cellular immunity, could regulate immune cells . To understand better the in vivo antitumor immune mechanism in distant tumors, the immunohistochemistry of CD86 and immunofluorescence of TNF‐α assays of distant tumors were conducted to research the mature of DCs and secretion of immune factor.…”
Section: Methodsmentioning
confidence: 99%
“…10-12 weeks later, mice were euthanized and their draining lymph nodes, spleen and a lower limb harvested. Lymph nodes and spleens were processed in to single cells suspensions as described previously [52] .…”
Section: Methodsmentioning
confidence: 99%
“…Using this approach, an implantable poly(lactideco-glycolide) (PLGA) based scaffold cancer vaccine was shown to induce complete melanoma regression in subsets of mice [27] . To eliminate the need for surgical implantation, we recently developed a new approach of injectable scaffolds using mesoporous silica rods (MSR) microparticles [28,29] . We demonstrated that MSR microparticles could spontaneously assemble into a 3D scaffold after subcutaneous injection; the macropores formed by random particle stacking allowed for cell infiltration and active cell-scaffold interactions.…”
Section: Introductionmentioning
confidence: 99%